2021
DOI: 10.1093/nar/gkab954
|View full text |Cite
|
Sign up to set email alerts
|

Targeting 3′ and 5′ untranslated regions with antisense oligonucleotides to stabilize frataxin mRNA and increase protein expression

Abstract: Friedreich’s ataxia (FRDA) is a severe multisystem disease caused by transcriptional repression induced by expanded GAA repeats located in intron 1 of the Frataxin ( FXN ) gene encoding frataxin. FRDA results from decreased levels of frataxin; thus, stabilization of the FXN mRNA already present in patient cells represents an attractive and unexplored therapeutic avenue. In this work, we pursued a novel approach based on oligonucleotide-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…Li et al . previously reported the use of ASOs to increase and stabilize mRNA levels for the yield of higher protein levels [ 34 ]. We hypothesized that the SHANK3 ASOs also have a stabilizing effect on SHANK3 mRNA levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Li et al . previously reported the use of ASOs to increase and stabilize mRNA levels for the yield of higher protein levels [ 34 ]. We hypothesized that the SHANK3 ASOs also have a stabilizing effect on SHANK3 mRNA levels.…”
Section: Discussionmentioning
confidence: 99%
“…For transfections, HEK293T were split into 12-well plates in a ratio corresponding to the desired culture time. Transfection times were chosen according to previously published data [ 34 , 41 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies have reported the potency of cocktails composed of non-gapmers or siRNAs [10][11][12], there have been no systematic evaluation of gapmer cocktails. Therefore, we evaluated combination-effect on the potency with 38 gapmer pairs targeting the same pre-mRNA.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the compounds in clinical development are based on gene silencing or splice switching. Multiple oligonucleotide-based activation mechanisms for gene activation have also been proposed, including promoter-targeted duplex RNAs ( 5–8 ), inhibition of repressive antisense transcripts ( 9 ), reducing noisy splicing ( 10 , 11 ), stabilizing mRNAs ( 12 ), enhancement of translation ( 13–16 ) and reducing nonproductive translation initiation ( 17 ). But to date, gene activation by oligonucleotides has proven to be significantly more challenging than gene silencing.…”
Section: Introductionmentioning
confidence: 99%